Secure control of cyber physical systems subject to stochastic distributed DoS and deception attacks - Mahmoud, Magdi S.; Hamdan, Mutaz M.; Baroudi, Uthman A. (International journal of systems science, 2020)
Cyber Physical Systems (CPS) such as power plants, water desalination utilities are just a few examples of systems that may come under stealth attacks. These attacks can threaten the proper operations of such systems without any indication. This problem necessitates the design of a control system that is able to work under such attacks. In this paper, an improved observer-based stabilising controller is proposed for CPS including random measurements and actuation delays and it is coming under distributed denial of service (DDoS) and deception attacks. The occurrences of DDoS and deception attacks are modelled as Bernoulli distributed white sequences with variable conditional probabilities. The criterion is presented in terms of linear matrix inequalities. Detailed simulation experiments on representative systems are shown to prove the applicability of the proposed methodology.